2022
DOI: 10.30802/aalas-jaalas-22-000025
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Sustained-release and Extended-release Buprenorphine in Mice after Surgical Catheterization

Abstract: The Guide for the Care and Use of Laboratory Animals strongly encourages the use of pharmaceutical-grade chemicals and analgesics. Sustained-release buprenorphine (SRB) is administered extralabel to rodents to mitigate moderate to severe pain. An FDA indexed buprenorphine formulation—extended-release buprenorphine (XRB)—has recently become available and is currently the only pharmaceutical-grade slow-release buprenorphine formulation approved for use in mice and rats. However, no studies have directly compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Since this review was prepared, additional studies have been published confirming the utility of LAI buprenorphine analgesics for animal medicine and the relative absence of skin lesions at the injection site with a lipid-based drug carrier. PK studies in Nu/Nu and C57Bl/6J mice [ 70 , 71 , 72 ] and neonatal Sprague Dawley rats [ 73 ] confirmed and extended the evidence supporting LAI buprenorphine products in laboratory animal research.…”
Section: Addendummentioning
confidence: 79%
“…Since this review was prepared, additional studies have been published confirming the utility of LAI buprenorphine analgesics for animal medicine and the relative absence of skin lesions at the injection site with a lipid-based drug carrier. PK studies in Nu/Nu and C57Bl/6J mice [ 70 , 71 , 72 ] and neonatal Sprague Dawley rats [ 73 ] confirmed and extended the evidence supporting LAI buprenorphine products in laboratory animal research.…”
Section: Addendummentioning
confidence: 79%
“…XRB (Ethiqa) is currently the only pharmaceutical grade FDA-indexed extended-release buprenorphine formulation that is approved for use in mice and rats. 29,57 In multiple strains of mice and rats, pharmacokinetic studies revealed a single injection of XRB (Ethiqa) provides therapeutic plasma concentrations for 48-72 h. 1,4,21,22,23,26,31,32,40 Additionally, XRB (Ethiqa) has a superior safety profile and long-lasting analgesia effects of up-to 72 h in mice and rats after a single subcutaneous injection. 3,7,16,19,24,40,48 Our results indicate in swine XRB (Ethiqa) provides longer therapeutic buprenorphine concentrations, consistent with what is observed in other non-rodent species and swine breeds.…”
Section: Discussionmentioning
confidence: 99%
“…29,57 In multiple strains of mice and rats, pharmacokinetic studies revealed a single injection of XRB (Ethiqa) provides therapeutic plasma concentrations for 48-72 h. 1,4,21,22,23,26,31,32,40 Additionally, XRB (Ethiqa) has a superior safety profile and long-lasting analgesia effects of up-to 72 h in mice and rats after a single subcutaneous injection. 3,7,16,19,24,40,48 Our results indicate in swine XRB (Ethiqa) provides longer therapeutic buprenorphine concentrations, consistent with what is observed in other non-rodent species and swine breeds. In the cynomolgus macaque ( Macaca fascicularis ) and the common marmoset ( Callithrix jacchus ), therapeutic buprenorphine plasma levels lasted as long as 96 h after XRB administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation